Brandbestattungen von der mittleren Donau bis zur Ägäis zwischen 1300 und 750 v. Chr. Akten des internationalen Symposiums an der Österreichischen Akademie der Wissenschaften in Wien, 11.-12. Februar 2010 - Lochner, Michaela (Verlag der Österreichischen Akademie der Wissenschaften, 2013)
In these conference proceedings particular attention is paid to the performance of burials and burial rites between 1300 and 750 BC. A change in burial customs took place in large parts of central Europe during the 13th century BC. The dead were no longer buried in inhumation graves - as was customary until then - but were burned and laid to rest in urns. This transformation of burial customs is probably connected to far reaching changes in society and religious beliefs.